The September 11 terrorist attacks - Hillstrom, Kevin, 1963- (Detroit, MI : Omnigraphics, 2012)
"Provides a comprehensive account of the origins of Islamic radicalism; the development of Osama bin Laden and al-Qaeda into a deadly force; the horrible events of September 11; the post-9/11 investigations; and the legacy of the 9/11 attacks. Includes a narrative overview, biographies, primary sources, chronology, glossary, bibliography, and index"--Provided by publisher.
Rage and despair in the Arab world -- Jihad in Afghanistan and the birth of Al-Qaeda -- Al-Qaeda emerges as a global threat -- The September 11 attacks on America -- Heartbreak and heroism on the ground -- Investigating 9/11 -- Missed clues and opportunities -- Legacy of the September 11 attacks.
Includes bibliographical references and index.
Keywords: September 11 Terrorist Attacks, 2001.; Terrorism -- United States; Qaida (Organization)